Jurnalisme Investigasi dalam Film Drama: Analisis Wacana pada Film FROST/NIXON - Muhammad Dhafa Oktavyandi; Septiawan Santana (Bandung Conference Series: Journalism, 2024)
Abstract. This research is motivated by film as a medium to display stories through moving images. The images are further put together with sounds, music, and effects that result in a more engaging experience for the audience. This study aims to determine the meaning of Micro discourse structures (semantic, syntactic, stylistic, and rhetorical) in Investigative Journalism on FROST/NIXON Films. This research uses a qualitative type of research. The discourse analysis method used is Van Dijk's theory because it can elaborate the elements of discourse so that it can be applied practically. The results of the study said that in this Frost/Nixon film, there is a tendency for journalists to carry journalistic discourse, especially those concerning the theme of Investigative Journalism. Frost/Nixon comes with a journalistic nuance that tells the story of David Frost as a journalist to find facts about Watergate by directly interviewing the alleged cause of the problem is very full because David dared to ask President Richard Nixon about the Watergate scandal. From the author's observations of the object of research, the author obtained the results of an analysis of investigative journalism discourse contained in the film Frost / Nixon. First, the structure of macro discourse in the film Frost / Nixon, the structure of macro discourse is a thematic element or commonly referred to as a theme referring to a general description in a text. Second, the superstructure of discourse in the film Frost/Nixon, Superstructure (Schematic) has three structures, including the core of the story, plot, and story structure. Third, micro discourse structures (semantic, syntactic, stylistic, and rhetorical) in Frost/Nixon. In the rhetorical observation unit there is a garfish close up and zoom in, then in the metaphor of circus animals performing and I imagine a jungle, dusty, dark, full of suffering, and loneliness, The expression in this film is anger and laughter. Abstrak. Penelitian ini dilatar belakangi oleh film sebagai media untuk menampilkan cerita melalui gambar yang bergerak. Gambar-gambar tersebut selanjutnya disatukan dengan suara, musik, dan efek yang menghasilkan pengalaman lebih menarik bagi para penonton. Penelitian ini bertujuan untuk Mengetahui pemaknaan struktur wacana Mikro (semantik, sintaksis, stilistik, dan retoris) dalam Jurnalisme Investigasi pada Film FROST/NIXON. Penelitian ini menggunakan jenis penelitian kualitatif. Metode analisis wacana yang digunakan adalah teori milik Van Dijk karena dapat mengelaborasi unsur-unsur wacana sehingga dapat diaplikasikan secara praktis. Hasil penelitian menyampaikan bahwa dalam Film Frost/Nixon ini, terdapat kecenderungan wartawan mengusung wacana jurnalistik terutama yang menyangkut tema Jurnalisme Investigasi. Frost/Nixon hadir dengan nuansa jurnalistik yang bercerita tentang David Frost sebagai wartawan untuk menemukan fakta perihal Watergate dengan langsung mewawancarai diduga penyebab masalah tersebut sangatlah fullgar karena David berani untuk bertanya secara kepada Presiden Richard Nixon mengenai skandal Watergate. Dari hasil pengamatan penulis terhadap objek penelitian, penulis mendapatkan hasil analisis wacana jurnalisme investigasi yang terdapat dalam film Frost/Nixon. Pertama, struktur wacana makro dalam film Frost/Nixon, struktur wacan makro yaitu elemen tematik atau biasa disebut dengan tema merujuk pada gambaran umum dalam suatu teks. Kedua, superstruktur wacana dalam film Frost/Nixon, Superstruktur (Skematik) memiliki tiga struktur antara lain inti cerita, plot, dan struktur cerita. Ketiga, struktur wacana mikro (semantik, sintaksis, stilistik, dan retoris) dalam film Frost/Nixon. Pada unit pengamatan retoris terdapat garfish close up dan zoom in, lalu pada metafora hewan sirkus yang sedang beratraksi dan aku membayangkan rimba, berdebu, gelap, penuh derita, dan kesepian, Ekspresi terdapat dalam film ini ialah marah dan tertawa.